Ответы и объяснения

2013-03-03T21:46:35+00:00

примечание: sin^2(x) = sinx в квадрате
=(1-sin8x) / ( sin4x-2cos^2(2x) + cos^2(2x) + sin^2(2x) )
=(sin^2(4x) + cos^2(4x) - 2*sin4xcos4x) / ( sin4x + sin^2(2x) - cos^2(2x) )

=(sin^2(4x) + cos^2(4x) - 2*sin4xcos4x) / ( sin4x - ( cos^2(2x) - sin^2(2x) ) )

=( sin^2(4x) - sin4xcos4x + cos^2(4x) - sin4xcos4x ) / ( sin4x - ( cos^2(2x) - sin^2(2x) ) )

=( sin4x*(sin4x-cos4x) - cos4x*(sin4x-cos4x) ) / ( sin4x - cos4x )

=( (sin4x-cos4x)*(sin4x-cos4x) ) / ( sin4x - cos4x )

= sin4x-cos4x